2010
DOI: 10.4314/ajbr.v11i3.50735
|View full text |Cite
|
Sign up to set email alerts
|

Review of paediatric neurological conditions seen in the physiotherapy department of a children’s hospital in ibadan, nigeria

Abstract: Management of paediatric neurological conditions involves a multidisciplinary team approach with Physiotherapy being an important member of the team. This study investigated the proportion that neurological conditions accounted for of the total number of paediatric conditions managed at the Physiotherapy Department of the Oni Memorial Children Hospital, Ibadan between January 2004 and December 2006 and also reviewed the specific neurological conditions. Records of all the patients managed during the study peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
3
3
0
Order By: Relevance
“…The most observed type of CP, based on motor function classification approach of assessing muscle tone, was the spastic type (91.1%) which is similar to that reported by other studies (Odding et al, 2006;Hamzat and Fatudimu, 2008;Ogunlesi et al, 2008;Frank-Briggs and Alikor, 2011), but with quadriplegic (62.9%) affectation dominating based on topography classification (pattern of paralysis) which is consistent with findings in some previous studies (Brigas-Grande et al, 2002, Singhi et al, 2002Hamzat et al, 2008;Peters et al, 2008;FrankBriggs and Alikor, 2011). This finding was however at variance with those of other researchers who reported a predominance of diplegic affectation among children with CP (Suzuki et al, 1999;el-Rifai et al, 1984).…”
Section: Types Of Cerebral Palsysupporting
confidence: 89%
See 1 more Smart Citation
“…The most observed type of CP, based on motor function classification approach of assessing muscle tone, was the spastic type (91.1%) which is similar to that reported by other studies (Odding et al, 2006;Hamzat and Fatudimu, 2008;Ogunlesi et al, 2008;Frank-Briggs and Alikor, 2011), but with quadriplegic (62.9%) affectation dominating based on topography classification (pattern of paralysis) which is consistent with findings in some previous studies (Brigas-Grande et al, 2002, Singhi et al, 2002Hamzat et al, 2008;Peters et al, 2008;FrankBriggs and Alikor, 2011). This finding was however at variance with those of other researchers who reported a predominance of diplegic affectation among children with CP (Suzuki et al, 1999;el-Rifai et al, 1984).…”
Section: Types Of Cerebral Palsysupporting
confidence: 89%
“…Cerebral palsy is recognized as a common childhood problem in Nigeria; however, most of the available data on CP in Nigeria are those generated from the limited area of practice of clinicians from various parts of Nigeria: Ibadan (Nottidge and Okogbo, 1991;Lagunju et al, 2006;Peters et al, 2008), Sagamu (Ogunlesi et al 2008), Port Harcourt (Frank-Brigges andAlikor, 2011). The main focus of the present study is to investigate the profile of children with CP referred for physiotherapy within wider practice settings embracing twelve selected secondary and tertiary hospitals in Southwest Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…The most observed type of CP was the spastic type (56.7%) which is similar to that reported by other studies (Odding et al, 2006;Hamzat and Fatudimu, 2008;Ogunlesi et al, 2008;Frank-Briggs and Alikor, 2011), with motor disorders (67.0%) dominating as the most common clinical presentation and is consistent with findings in some previous studies (Singhi et al, 2002;Hamzat et al, 2008;Peters et al, 2008;Frank-Briggs and Alikor, 2011).…”
Section: Types Of Cerebral Palsy and Clinical Presentationssupporting
confidence: 91%
“…It is also supported by a study conducted in Nigeria which showed that CP was accounted (43.7%) for the majority of the cases visiting the physical therapy department. 28 In general, through an interdisciplinary inpatient rehabilitation approach, children made significant changes from admission to discharge, which is supported by the previous studies that reported an overall change in outcomes after rehabilitation. 2,5,14,17,18,[29][30][31] Functional gains, as measured by the Wee-FIM instrument, vary depending on diagnoses, time from injury/diagnosis to rehabilitation admission, age, and LOS.…”
Section: Discussionsupporting
confidence: 64%